ANALISIS REGULASI EMOSI SISWA DITINJAU BERDASARKAN GENDER DALAM MENYELESAIKAN SOAL CERITA PADA SISWA KELAS VII UPTD SMP N 1 AEK KUASAN - Jelia Arika; Syahriani Sirait (MES: Journal of Mathematics Education and Science, 2026)
This study aims to describe students’ emotional regulation based on gender in solving word problems on fraction material. This research employed a qualitative descriptive approach involving 27 seventh-grade students at UPTD SMP Negeri 1 Aek Kuasan, consisting of 16 male students and 11 female students . Data were collected through tests, questionnaires, observations, interviews, and documentation. The results showed that students' emotional regulation was categorized into high, medium, and low levels. Most students were in the medium category (40.7%), followed by high (29.6%) and low (29.6%) categories . Based on gender, female students tended to have better emotional regulation than male students, as indicated by a higher percentage in the high category. These findings indicate that emotional regulation plays an important role in helping students remain calm, focused, and systematic in solving mathematical word problems. Therefore, emotional aspects should be considered in mathematics learning, especially when dealing with complex problems.